Clinical Trials in Recurrent Ovarian Cancer. Issue 4 (1st April 2011) - Friedlander, Michael; Trimble, Edward; Tinker, Anna; Alberts, David; Avall-Lundqvist, Elisabeth; Brady, Mark; Harter, Philipp; Pignata, Sandro; Pujade- Lauraine, Eric; Sehouli, Jalid; Vergote, Ignace; Beale, Philip; et al.
Abstract : The 4th Ovarian Cancer Consensus Conference of the Gynecologic Cancer InterGroup was held in Vancouver, Canada, in June 2010. Representatives of 23 cooperative research groups studying gynecologic cancers gathered to establish international consensus on issues critical to the conduct of large randomized trials. Group C, 1 of the 3 discussion groups, examined recurrent ovarian cancer, and we report the consensus reached regarding 4 questions. These included the following: (1) What is the role of cytoreductive surgery for recurrent ovarian cancer? (2) How do we define distinct patient populations in need of specific therapeutic approaches? (3) Should end points for trials with recurrent disease vary from those of first-line trials? (4) Is CA-125 progression alone sufficient for entry/eligibility into clinical trials?